The Potential for Servant Leadership to Raise Teacher Morale in Primary Schools: Perspectives from South Africa - Roseline Makirimani; Suraiya Rathankoomar Naicker (SAGE Open)
The aim of this study was to investigate whether the enactment of servant leadership could be a prospective strategy to raise teacher morale. First, the factors that cause poor teacher morale were sought. Second, the perspectives of teachers and principals regarding the notion of servant leadership in improving teacher morale were pursued. A generic qualitative approach was employed and data was collected from four principals and eight teachers by means of individual interviews. Insufficient support from principals, lack of involvement of teachers in decision-making, leadership styles of principals, and work-related factors were the main causes of poor teacher morale. Teachers and principals both agreed that servant leadership could contribute to raising teacher morale. The study was conducted when teaching and learning resumed after the Covid-19 lockdown. Therefore, the data collection was limited to one school district and the methodology limited to individual interviews, both online and face-to-face. The study led to the formulation of eight standards that leaders could use in their leadership practice.